Instilling Ethics and Moral Education in Early Childhood at the An Nur Orphanage in Medan - Maraendar, Akbar; Azzura, Diva; Dalimunthe, Elvi Susana; Butar-Butar, Gracia Patunia; Simanjuntak, Ririn Ayu; Sihite, Visensia; Rachman, Fazli (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Ethical and moral education for children is a long-term investment to form a generation with character in the future, so it is necessary to instill the formation of ethics and morals in children from an early age, whether at school, at home, in the environment and society and so on. Therefore, this research was carried out as a strategy to instill ethical and moral education in young children, especially nowadays at the An Nur Medan orphanage. This research uses qualitative research methods with data collection techniques carried out by means of literature study by understanding and studying theories from various literature related to research. This research produces several strategies that can be used to instill ethical and moral education, namely through routine activities such as praying together before eating, then through spontaneous activities, for example giving advice or understanding to children who give and receive using their left hand, and finally through activities. "Role model", in this case the adult plays a direct role as an example for the child. The conclusion of this research is that basically providing moral education from an early age can help children have a positive attitude, respect every other human being and make morals an inseparable bond for every child as they grow and develop into adulthood.